Effect of mangostin on the functional activity and integrity of the Plasmodium falciparum and infected and Uninfected red blood cells membrane - Ibraheem, Z.O.; Majid, R.A.; Noor, S.M.; Farook, M.D.; Basir, R. (Parasitology and Public Health Society of Nigeria, 2024)
Mangostin is a natural xanthanoid obtained from various parts of the mangosteen tree Garcinia mangostana with diverse medicinal effects, such as; antioxidant, antibacterial, anticancer and anti-inflammatory. This study aimed at exploring its impact on the integrity, and the physiological function of both Plasmodium falciparum-infected and uninfected red blood cells (RBCs). This was achieved by studying its impact on the RBCs morphology, integrity and osmotic fragility. On the one hand, its effect on the plasmodium-infected cells was achieved by screening its impact on the parasite-induced new permeation pathways (NPPs) and the plasmodial invasiveness to the RBCs and these were related to its growth inhibitory effect against the parasite. On the other hand, its molecular characteristics were determined using the In Silico Molispiration simulation software and its anti-oxidant activity was measured using conventional in vitro tests and the anti-lipid peroxidation assay. The results showed that mangostin had a good growth inhibitory effect against Plasmodium falciparum with a moderate selectivity as compared to its effect against RBCs. Furthermore, it showed a good inhibitory effect against merozoite invasion and the plasmodium-induced new permeation pathway at concentrations less than the cytotoxic dose against RBCs and the parasite. Besides it succeeded in hampering the oxidative stress-induced RBCs damage without affecting the RBC fragility when it was added at low doses. Overall, the results suggest that their anti-plasmodium effect is not related to their impact on the RBCs membrane. Further studies are recommended to explore their precise mechanism of action.